Analisis Pengaruh Indeks Pembangunan Manusia dan Inflasi Terhadap Pertumbuhan Ekonomi Pada 6 Provinsi di Indonesia Tahun 2017-2021 - Naufal Nur Wibowo (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The aim of this study is to analyze and measure the factors affecting Indonesia's economic growth rate by focusing on a number of factors, such as the human development index and inflation. The study use eviews10 software with its fixed effect model (fem) to see its enormous value of determinations and correlation between non-monetary variables and variables. The data studied came from the statistical central body in Indonesia, as well as several literature studies ranging from 2017 to 2021. From research and theoretical studies itis concluded that in 2017-2021 there is no effect between the human development index and inflation and economic growth in Indonesia.